Noisy trains - Priddy, Roger (New York : Priddy Books, 2010)
Pages feature bright illustrations of favourite tractors and trains, with simple text to listen to or read. Each book has an integral sound button for little fingers to press, so that children can hear sounds like the tractor's engine or the train's whistle. Encourage speaking skills, help to develop hand-eye coordination and build early vocabulary.
C
b
b
Keywords: Trains -- Noisy